Epidemiologia molecular e riscos associados ao portador nasal de Staphylococcus aureus isolados de crianças de creches de Goiânia - CARDOSO, Juliana Lamaro (2009)
Objectives: (i) to assess the prevalence of Staphylococcus aureus and methicillin-resistant S. aureus (MRSA) nasal carriage in children attending day-care centers (DCC) in the municipality of Goiânia; (ii) to determine the potential risk factors related to S. aureus carriage and MRSA; (iii) to characterize MRSA isolates circulating in DCCs using molecular typing methods. Methods: Between August and December 2005, nasal swabs were collected from children who attended 62 DCCs. Clinical and socio-demographic information associated with the acquisition of S. aureus and MRSA were obtained through questionnaires applied to parents or guardians. The swabs were processed following the standard methods for identification and isolation of S. aureus. Amplification femB gene by polymerase chain reaction (PCR) was used to confirm the specie. The presence of mecA gene was detected by PCR and the positive isolates were identified as MRSA. Susceptibility to MRSA was determined by disk diffusion method. MRSA molecular typing was performed by PFGE, MLST, spa typing and SCCmec multiplex PCR. Results: 371 (31.1%) out of the 1.192 collected swabs were positive for S. aureus and 14 (1.2%) were identified as MRSA. The factors independently associated with risks for nasal colonization by S. aureus were children higher than two years of age (OR = 1.83, 95% CI 1.27-2.65) and previous DCC attendance (OR = 1.48; 95% CI 1.01-2.16). Mother s high degree of education was a protective factor for S. aureus carriage (OR = 0.43, 95% CI 0.23-0.80). A multidrug resistant dominant MRSA lineage was identified comprising 8 out of the 14 MRSA isolates. This cluster was characterized as SCCmec type IIIA, ST239 and spa type t037 sharing 82.7% genetic similarity with the Brazilian clone. One MRSA strain was classified as SCCmec type V and ST1120. This strain showed features of CA-MRSA although it has been recovered from a healthy child who presented risk factors for HA-MRSA acquisition. The remaining MRSA strains showed a diverse genetic background. Conclusions: Children attending DCCs are often colonized with S. aureus and although the prevalence of MRSA was low, they can represent potential vectors of spread of resistant pathogens to the community. The detection of a MRSA lineage circulating within DCCs suggests a two-way flow spread of MRSA between hospitals and community.